Politeness Strategies Used by Trump and El-Sisi in Their Speeches at United Nations Assembly - Ummi Ashim Azzahra; Hendi Pratama; Mursid Saleh (English Education Journal, 2023)
In this study, the researchers identified ways that politeness strategies are commonly employed in a speech. Specifically, this study aimed at exploring the politeness strategies used by Donald Trump and General El Sisi during their speech at the 75th session of the UN General Assembly. Both the similarities and the differences between Donald Trump’s and General Sisi's use of politeness strategies and sub-strategies in their speeches were investigated. A qualitative research approach was conducted, and the theory of politeness strategies by Brown and Levinson was applied as the analysis framework. The research data was collected from the 57 utterances in Trump's speech and 79 utterances in General Sisi's speech. The analysis results showed that both Trump and El-Sisi applied bald on record, positive, and negative politeness. Specifically, the politeness strategies found in Trump's speech were 10 utterances of bald on record, 53 utterances of positive politeness, 8 utterances of negative politeness, and two utterances of off-record strategy. On the contrary, General Sisi's speech mostly contained negative politeness strategies. It was found that there were 70 utterances of negative politeness, 11 utterances of positive politeness, and 1 utterance of off-record strategy. These various politeness strategies used by Donald Trump and General Sisi could not be separated from their respective social positions, social distances, and cultural backgrounds.